A Review of Membrane Bioreactor Technology for Industrial Wastewater - Askar, Ahmed S. Abd (American Journal of Biology and Natural Sciences, 2026)
In this study, the operation, activation, process and use of membranes in bioreactors in wastewater treatment are explained. The membrane bioreactor (MBR) method is a simple, one-step method that combines a membrane-bound bioreactor with visualization and description of the activated sludge process. The activated sludge plant can be operated in a single step and when used as MBR, high quality wastewater that can be recycled can be produced. The robustness of MBR technology also attracts attention in wastewater treatment. Theoretically, maintaining longer SRTs in MBRs promotes the growth and survival of certain microorganisms, which can improve the removal of refractory materials and enhance energy production for destruction and exchange. Published studies show that the theoretical expectation of improving the biodegradation of compounds with low biodegradability in MBRs is not always met. This review first introduces the basic concepts of MBR tools and then describes the latest developments in all MBR tools. The characteristics of the bioreactor purification process are discussed in depth, and then the membrane separation process is examined. The consequences of scaling, which is a major issue in the adoption of MBR facilities, and recent scaling reduction methods are discussed in detail. Many efforts regarding the new MBR process have been documented. Current issues and future research to resolve the current limitations of MBR and make it more applicable on a larger scale are presented.